What is the derivative of f(x)=-2x^-3+x^2-7? Calculus Basic Differentiation Rules Power Rule 1 Answer Guilherme N. Jan 6, 2016 Recalling the power rule, which states that, for y=x^n, then y'=n*x^(n-1), we can proceed: Explanation: (df(x))/(dx)=(-3)(-2x^(-4))+2x (df(x))/(dx)=6x^-4+2x Answer link Related questions How do you find the derivative of a polynomial? How do you find the derivative of y =1/sqrt(x)? How do you find the derivative of y =4/sqrt(x)? How do you find the derivative of y =sqrt(2x)? How do you find the derivative of y =sqrt(3x)? How do you find the derivative of y =sqrt(x)? How do you find the derivative of y =sqrt(x) using the definition of derivative? How do you find the derivative of y =sqrt(3x+1)? How do you find the derivative of y =sqrt(9-x)? How do you find the derivative of y =sqrt(x-1)? See all questions in Power Rule Impact of this question 1548 views around the world You can reuse this answer Creative Commons License